2015
DOI: 10.1007/s10339-015-0725-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates of embodiment and motivational factors during the perception of virtual architectural environments

Abstract: The recent efforts aimed at providing neuroscientific explanations of how people perceive and experience architectural environments have largely justified the initial belief in the value of neuroscience for architecture. However, a systematic development of a coherent theoretical and experimental framework is missing. To investigate the neurophysiological reactions related to the appreciation of ambiances, we recorded the electroencephalographic (EEG) signals in an immersive virtual reality during the apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 19 publications
1
36
0
2
Order By: Relevance
“…Thus, VR makes it possible to simulate and evaluate spatial environments under controlled laboratory conditions 32 , 33 , allowing the isolation and modification of variables in a cost and time effective manner, something which is unfeasible in real space 34 . During the last two decades VR has usually been displayed using desktop PCs or semi-immersive systems such as CAVEs or Powerwalls 35 . Today, the use of head-mounted displays (HMD) is increasing: these provide fully-immersive systems that isolate the user from external world stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, VR makes it possible to simulate and evaluate spatial environments under controlled laboratory conditions 32 , 33 , allowing the isolation and modification of variables in a cost and time effective manner, something which is unfeasible in real space 34 . During the last two decades VR has usually been displayed using desktop PCs or semi-immersive systems such as CAVEs or Powerwalls 35 . Today, the use of head-mounted displays (HMD) is increasing: these provide fully-immersive systems that isolate the user from external world stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Design neurocognition EEG-based studies are emerging at an exploratory stage with a few reported domain-specific studies on engineering design, architecture and industrial design. Results from controlled experiments identify the relationship between design problem statements and cognitive behaviors during conceptual design (Liu et al, 2018), visual attention and association in expert designers (Liang et al, 2018), neurophysiological EEG signals to study effort, fatigue and concentration in conceptual design (Nguyen et al, 2016), EEG bands associated with the design activities of problem solving and evaluation (Liu et al, 2016), neurophysiological correlates of embodiment and motivational factors during the perception of virtual architecture (Vecchiato et al, 2015). However, time-related neural responses during problem-solving compared to design tasks across domains are as yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, there is an increasing interest for studying perception of architecture in terms of multi-sensory and embodied experience, understood in the context of late-nineteenth century empathy theories and inspired by recent conceptual and experimental neuroaesthetic framework by Freedberg and Gallese ( 2007 ). Accordingly, initial studies investigated how spatial features modulate bodily self-consciousness (Pasqualini et al, 2013 ) and explored the possibility to understand neurophysiological correlates of architectural perception pertaining to cerebral circuits involved in embodiment, sensorimotor integration, and spatial navigation (Vecchiato et al, 2015a , b ). As elaborated later on, the proposed enactive approach for understanding architectural experience is directly based on this closely related line of research dedicated to the study of embodiment in art experience.…”
Section: Introductionmentioning
confidence: 99%